Die Kleinschmetterlinge (Microlepidoptera) der Diluviallandschaften um Eberswalde - Richert, Arnold; Busse, Rainer; Theimer, Franz; Schwabe, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 2020)
Microlepidoptera have been the subject of entomological research in Eberswalde since the first half of the 19th Century. Centres of research were at first the forestry colleges and institutes, later also the German Entomological Institute. Furthermore, the Eberswalde area has always been a magnet for many Microlepidoptera specialists who did not work at scientific institutes.In this paper the results of past research are evaluated faunistically at the regional level and supplemented by data obtained during recent research. The result is a list of Microlepidoptera of the diluvial landscapes around Eberswalde. Comprising 863 species in 47 families, the inventory includes 57 % of the Microlepidoptera species found in the state of Brandenburg, including a species not previously recorded in Germany: Clepsis coriacanus; 13 new finds for the state of Brandenburg: Coleophora adjectella, Colephora sylvaticella, Coleophora ramosella, Mompha terminella, Monochroa arundinetella, Bryotropha umbrosella, Anarsia innoxiella, Telephila schmidtiellus, Cydia gemmiferana, Acrobasis legatea, Pammene herrichiana, Pammene ignorata, Schreckensteinia festaliella; and 45 rediscoveries for the State of Brandenburg. The authors were able to record 332 species for the first time in the Eberswalde area. For 531 species older/ historical evidence was evaluated. The occurrence of 408 of these species is confirmed.The record data are presented in tabular form and assigned both to the classification of natural areas of the region and to the map sheets of the ordinance survey.
Keywords: Faunistics; Brandenburg; Microlepidoptera; Collections